Impact of Profitability On The Market Value of Bank Shares Case Study of The International Islamic Bank of Syria (Journal of Hama University, 2021)
This study aimed to identify the effect of profitability on the market value of the shares of Syria International Islamic Bank during the time period from 2010 to 2019, depending on the profitability ratios represented by (rate of return on equity and rate of return on assets), and the method of regression analysis was used. The simple study of the impact between the two variables, depending on the statistical analysis program SPSS, and the results of this study found that there is no effect between the profitability ratios and the market value of the shares of Syria International Islamic Bank.